Integrasi Ilmu Sosial yang Bersumber dari Al-Quran dan Hadis - Nurazizah; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This paper quotes verses from the Qur'an and hadiths of the Prophet Muhammad (PBUH) that talk about the social problems faced by Muslims and integrate with new ideas that give birth to a branch of social science. A good Muslim is one who is able to maintain good relations with his fellow human beings (ḥablu min an-nās) and good relations with his Lord (ḥablu min Allāh). People who are able to interact and maintain good relations with society are indicators of their good relationship with God. Social interaction is a necessity for every living human being. Man was created by Allah Almighty as a personal being as well as a social being. The relationship between one individual and another in a community, of course, requires rules and guidelines. Without clear rules and certain boundaries, it is certain that human life will experience chaos and destruction. The Qur'an and the hadith of the prophet Muhammad (peace be upon him) provide signs as a guide to human relations in life. The relationship of a Muslim is required to always refer to the instructions of the Qur'an and the hadith.